DEVELOPING AUGMENTED REALITY FOR IMPROVING CONCEPT COMPREHENSION ON PHOTOGRAPHY LEARNING - Ananda, A. Suci Rizky; Haryanto, Haryanto (Universitas Muhammadiyah Mataram, 2025)
Integrating Augmented Reality (AR) in vocational high schools presents a transformative opportunity for vocational education; however, its efficacy hinges critically on teachers' acceptance and pedagogical adaptation. This study explores vocational high school teachers' views on using Augmented Reality (AR) to enhance practical learning and student engagement in vocational education. Augmented reality holds great potential as a learning tool, especially in the Visual Communication Design department at Vocational High School. This qualitative study employed a phenomenological research design to examine vocational teachers' lived experiences with augmented reality (AR) in instruction. Six purposively selected vocational teachers from West Sulawesi, Indonesia, participated in semi-structured in-depth interviews, enabling detailed exploration of their perceptions, challenges, and contextual adoption strategies. Thematic analysis was performed using ATLAS.ti 2023, revealing two key themes: the strengths and weaknesses of PowerPoint or Canva media, and the benefits of augmented reality. The study found that while PowerPoint or Canva had more weaknesses than strengths for photography subjects, augmented reality proved to be highly effective in improving student comprehension, thanks to its 3D features and new technology. Schools should prioritize teacher training programs, implement pilot projects in specific technical fields, and foster government-industry partnerships for resource support to maximize AR's potential. Future research should focus on longitudinal studies of AR's educational impact and the development of affordable, customizable AR solutions tailored to vocational training needs, ensuring this technology effectively bridges the gap between classroom learning and workplace skill requirements.